Dose response of chitosan on nutrient digestibility, blood metabolites and lactation performance in holstein dairy cows - Mingoti, R. D. (2016)
Chitosan (CHI), a non-toxic and biodegradable biopolymer has been successfully used in the food, human and veterinary medicine industries, especially because of its antimicrobial properties. This study aimed to investigate the effects of CHI on dry matter intake (DMI), nutrient digestibility, blood metabolites, milk yield and composition, and milk fatty acids profile of lactating dairy cows. Sixteen Holstein cows (91.3±15.1 days in milk, 29.8±4.1 kg/d of milk, 610±55 kg of body weight [BW]) were used in a 4×4 Latin square design, and each experimental period consisted of 14 days of diet adaptation and 7 days for data collection. Animals were allocated to receive one of treatments: C0: basal diet, without CHI addition; C50, C100 and C150 received 50, 100 and 150 mg/kg BW of CHI, respectively. Chitosan addition did not affect DMI, but increased (P≤0.05) the digestibility of dry matter (DM), organic matter (OM), crude protein (CP) and neutral detergent fiber (NDF). Blood urea nitrogen concentration was increased (P=0.01) with CHI addition. Chitosan decreased (P=0.02) nitrogen (N) fecal excretion without affect nitrogen balance. There was no effect of CHI on milk yield, fat corrected milk, and milk composition. Chitosan decreased (P≤0.05) C6:0 and C18:1 c9, and quadratically affected C14:1 fatty acids (FA) concentration in milk fat. Chitosan had no effect on total saturated and unsaturated FA of milk fat. Chitosan improved nutrient digestibility without affect productive performance and milk fatty acid profile of mid-lactation dairy cows.